Incidence of Hepatitis B Due to Multiple Transfusions in Patients of β-Thalassemia Major: Incidence of Hepatitis B in Patients of β-Thalassemia Major - Naz, Rida; Ullah, Farman; Muhammad, Taj; Khan, Obidullah; Shah, Faridullah; Rehman, Aziz u; Basir, Noor Ul (Pakistan Journal of Health Sciences, 2023)
β-Thalassemia is one of the most prevalent childhood hemolytic disorders. Multiple blood transfusions of unscreened blood can result in infection transmission. After many transfusions, Hepatitis B infection in thalassemia patients was reported. Objective: To determine the incidence of Hepatitis B in β-thalassemia major patients, associated with multiple blood transfusion strategies. Methods: This cross-sectional study was executed in Pediatric department of DHQ teaching hospital Dera Ismail khan with the collaboration of the Regional Blood center, and comprised 360 patients, diagnosed with β-Thalassemia Major and maintained on multiple transfusions. Results: The average weight of the subjects was 43.50+18.76 Kg and their mean age was 13.10+2.1 years. The significantly high population of the patients (p<0.05) was not immunized against Hepatitis B (73.88%), while only 26.66% (94/360) were immunized. The patients having less than 10, 11-20 and more than 20 transfusions per annum comprised 72 (20%), 157 (43.61%) and 131 (36.38%) patients, respectively. The affected patients had significantly altered hematological parameters (p<0.05). The highest number of β-Thalassemia Major patients affected with Hepatitis B belonged to the Group having more than 25 transfusions of blood annually, with an incidence rate of 11.53. Conclusions: The greatest risk factor for Hepatitis B infection in β-thalassemia major patients is concluded to be multiple blood transfusions. It was also found that a huge population of Thalassemia patients was not immunized against HBV despite the severe risk. Therefore, health education and awareness campaigns are needed for the significance of Hepatitis B immunization and transfusion of screened blood.